2012
DOI: 10.5121/sipij.2012.3601
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Feature Extraction Techniques in Face Recognition

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Image feature can be obtained after the color space of the image is specified. Features resulted in a variety of research on the color feature are histograms, color moments (CM), color coherence vector and the color correlogram [5,8,9,10,11,12]. There is dominant color descriptor (DCD), color structure descriptor (CSD), and Scalable color descriptor respectively for color feature extraction [13].…”
Section: Feature Extraction Of Color Texture and Shapementioning
confidence: 99%
See 2 more Smart Citations
“…Image feature can be obtained after the color space of the image is specified. Features resulted in a variety of research on the color feature are histograms, color moments (CM), color coherence vector and the color correlogram [5,8,9,10,11,12]. There is dominant color descriptor (DCD), color structure descriptor (CSD), and Scalable color descriptor respectively for color feature extraction [13].…”
Section: Feature Extraction Of Color Texture and Shapementioning
confidence: 99%
“…In general, a method for extracting texture feature can be divided into two categories based on spatial domain (spatial texture) and frequency domain (spectral texture). Spatial texture feature is obtained by calculating the statistical values of the pixel or finding a local pixel structure in the original image [10]. Spectral texture feature is obtained by making a transformation into the frequency domain and calculating features from the image transformed.…”
Section: -3mentioning
confidence: 99%
See 1 more Smart Citation
“…Face recognition was deeply studied through the last decades [1]. Several types of features were presented with different levels of recognition accuracy [2]. Each type of feature represent an amount of information extracted from the image, and more represented information in chosen feature provides more accuracy in recognition results [3].…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, Rouhi et al [8] have tested and analysed several other feature extraction methods namely Gabor Filter, and Elastic Bunch Graph Matching (EBGM). Rouhi et al [8] found that 15-Gabor filter with fuzzy filter leads to a high rate of the feature extraction in the face recognition.…”
Section: Introductionmentioning
confidence: 99%